Jak nas czytają za granicą? Ankieta - Pelurityte-Tikuisiene, Audinga (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
Audinga Peluritytė-Tikuišienė shows that despite the common history and treating the contemporary Polish culture and language as a bridge to Europe, Lithuanian writers are turning more toward the East. The author herself, when comparing the style reception in different countries of Central and Eastern Europe, notices psychologism, spirituality, anthropocentric and subjective interpretations of works important in Polish literary theory. She especially values the work of Polish neoclassical writers and comparative writings, noting the need for translations into Lithuanian.